Higher Education and Indigenous Students in Oaxaca: Problems and Challenges - Reyes Pérez, Omar de Jesús (2013)
College students from Indigenous groups face particular challenges that add up to the challenges of taking a university major. As if this were not enough, styudying a major in one of the poorest Mexican states and with a lower academic level in the country poses extraordinary efforts to the students to complete their majors successfully. This paper presents some of the challenges faced by indigenous students studying at “Universidad del Mar,” Huatulco Campus.